Cultural value and cultural policy: some evidence from the world of live music. Issue 3 (26th May 2016) - Behr, Adam; Brennan, Matt; Cloonan, Martin
Abstract : This article considers live music policy in relation to wider debates on the cultural (as opposed to instrumental) value of the arts. The findings are based on research into amateur/enthusiast, state-funded and commercial concerts across a range of genres – classical, traditional folk, jazz, singer–songwriter and indie – using the Edinburgh Queen's Hall venue as a case study. We argue that (1) articulations of the cultural or intrinsic value of live music across genres tend to lapse back into descriptions of instrumental value; (2) although explanations vary from audiences, artists and promoters as to why they participate in live music, they also share certain characteristics across genres and sometimes challenge stereotypes about genre-specific behaviours; and (3) there are lessons to be learned for live music policy from examining a venue that plays host to a range of genres and promotional practices.